(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Carbon fiber composites are being widely considered for many classes of heavily loaded components. A common feature of such components is the need to introduce local or global loads into the composite structure. The use of adhesive bonding rather than mechanical fasteners offers the potential for reduced weight and cost. The use of carbon fiber reinforced plastics (CFRP) for the repair of steel structure is also advantageous, for example to avoid welding or bolting which can weaken structure and add fire risk. This study is based on adhesive bonded double lap shear (DLS) joints where the inner adherend is steel and the outer adherend is cross plies unidirectional (UD) CFRP. Overlap lengths of 25-125 mm with CFRP thickness of 3 and 6 mm were considered and two different orientation angles [0o,90o] and [90o,0o] laminates have been considered. The overall objectives of the paper are to investigate the delamination of the CFRP laminates within the DLS joints under quasi-static loading and both experimental and numerical techniques were used. The numerical study was based on 2-D model using strength-limit method, taking into consideration the UD properties of the plies and the resin layers separating these. As a result, it was concluded that the data obtained from 2-D finite element analysis were coherent with experimental results and additional to that fiber orientation angles of the laminate markedly affected the failure load of joints, failure mode and stress distributions appeared in adhesive and composite